Pedagogical situations: interpretation difference - Victoria V. Dobrova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Taking into account the need to clarify the terminological framework of modern pedagogy, the concept pedagogical situation in general and its place in the pedagogical discourse in a cross-cultural aspect is discussed. Today, the concept of situation gains a general methodological significance though lacks a clear definition. Based on the analysis of interdisciplinary research, we concluded that the integral concept of situation includes: presence of subjects, dynamism, external conditions, causal relations, chronotope. The analysis of scientific sources proved that in pedagogical discourse of Russian- and English-speaking authors the term pedagogical situation is used incorrectly, the concept of pedagogical situation is mistaken for other pedagogical categories at the theoretical level, there is no unified approach to its definition. Thus the pedagogical situation analysis in Russian language pedagogical discourse is centred on the formulation of a pedagogical task, and in the English-speaking pedagogical tradition it is based on the triangle diagram that includes a teacher, a student and content. In the conducted cross-cultural and partly interdisciplinary study, a pedagogical situation is conventionally understood as a process of interaction of subjects of pedagogical activity (educational process) with a certain task in a certain place and time.